2) x + y + z = 189
x ÷ y = 3, rest 4
y ÷ z = 3, rest 4
------------------------
Teorema imparitii cu rest: D = I · C + R, unde R < I
x = 3y + 4
y = 3z + 4
Inlocuim:
x + y + z = 189 ⇔ (3y + 4) + (3z + 4) + z = 189
⇒ 3y + 8 + 4z = 189 ⇒ 3(3z + 4) + 8 + 4z = 189
⇒ 9z + 12 + 8 + 4z = 189
⇒ 13z + 20 = 189
⇒ z = (189 - 20) ÷ 13
⇒ z = 13
Deci:
y = 3z + 4 = 3 · 13 + 4 = 43
x = 3y + 4 = 3 · 43 + 4 = 133
3) x = y + 155
x ÷ y = 3, rest 9
---------------------
x = 3y + 9 ⇒ 3y + 9 = y + 155 ⇒ 2y = 106 ⇒ y = 53
x = 53 + 115 = 168
x + y = 168 + 53 = 221